Buccal Cortical Bone Thickness in Iraqi Arab Adults by Cone Beam Computed Tomography for Orthodontic Mini-Implants - Abbas, Saad A.; Alhuwaizi, Akram F. (Journal of Baghdad College of Dentistry, 2017)
ABSTRACTBackground: Cortical bone thickness is important for the stability of mini implants. Placing mini implants in sites of favorable cortical bone thickness would guarantee better initial stability and long-term success. The aim of this study was to investigate gender, side and jaw differences of the buccal cortical bone thickness as a guide for orthodontic mini screw placement.Materials and Methods: The sample was selected from the patients attending the Specialized Health Center in Al-Sadr City / 3D department. Thirty patients (15 males and 15 females) were selected and cone beam computerized tomographic images were done. Then the buccal cortical bone thickness was measured at thirteen inter radicular sites in the maxilla and mandible from the mesial side of the second molar to the mesial side of the second molar on the other side. The resulting data were statistically analyzed using independent t-test on SPSS program.Results: The buccal cortical bone thickness of the males was more than the females for both jaws. The mandibular buccal cortical bone thickness was thicker than in the maxillary and in the anterior region was thinner than in the posterior region for each jaw. The thickness of the buccal cortical bone was generally greater on the left side